Makna Kekudusan Hidup Umat Tuhan: Tinjauan Eksegesis Berdasarkan Imamat 19:2 - Refamati Gulo (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2024)
Holiness is the absolute standard for believers. A holy God requires His people to live in holiness. There are many studies that discuss holiness, but this paper finds that there is a deep meaning and special emphasis in Leviticus 19:2 that should be considered and explored further. Based on the descriptive method, literature study and exegetical analysis, this research finds two implications for believers regarding holiness, namely being born again as the basis for every believer to experience cleansing from the old life, and avoiding uncleanness as a commitment to live pleasing to God. This research encourages all believers to continue to live righteously and maintain holiness so that their lives become an example and have an impact.